Vers une esthétique environnementale ? Regards sur un colloque - Blanc, Nathalie (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2010)
The Esthétique environnementale network emerged in France in 2007, produced by the intersection and complementarity of certain evolving thematic matrices: the mobilization of the public, nature and the urban landscape, and artistic creation. This network has grown since 2004 out of the original research centres of its developers, the UMR LADYSS (Nathalie Blanc) and the UMR PACTE (Jacques Lolive). Through their joint action, an issue of the journal Cosmopolitiques, “Aimons la ville,” was produced (Éditions de l’Aube, 2004), three research seminars were presented (2006) with a joint publication as a result, and a research project was conducted through the MEDD program, “Paysage et développement durable.” Finally, an international conference entitled Environnement, engagement esthétique et espace public was held in Paris in 2007. More than a hundred internationally known participants were gathered at the conference, allowing the formation of a network of researchers interested in this multi-faceted thematic (ambiences, landscapes, environmental aesthetics, ethics, ecological art, etc.). A publication followed the conference (2010). While acknowledging that the field of environmental aesthetics is still young, this article includes a report of the conference and its principal contributions.